1994
DOI: 10.1128/mcb.14.10.6727
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the platelet-derived growth factor beta receptor signaling pathway activates protein kinase C-delta.

Abstract: The murine myeloid progenitor cell line 32D was recently shown to undergo monocytic differentiation when protein kinase C-delta (PKC-delta) was overexpressed and activated by 12-O-tetradecanoylphorbol-13-acetate (TPA) (H. Mischak, J.H. Pierce, J. Goodnight, M.G. Kazanietz, P.M. Blumberg, and J.F. Mushinski, J. Biol. Chem. 268:20110-20115, 1993). Tyrosine phosphorylation of PKC-delta occurred when PKC-delta-transfected 32D cells were stimulated by TPA (W. Li, H. Mischak, J.-C. Yu, L.-M. Wang, J.F. Mushinski, M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
101
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(114 citation statements)
references
References 19 publications
(26 reference statements)
11
101
2
Order By: Relevance
“…Several reports showed that tyrosine-phosphorylated PKC␦ had decreased activity (25,28,35), whereas others indicated the opposite (16,40) or reported a modulation in its substrate specificity (24). Li et al (43) had identified Tyr-187 as a phosphorylation site in PKC␦ upon 12-O-tetradecanoylphorbol-13-acetate or platelet-derived growth factor stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports showed that tyrosine-phosphorylated PKC␦ had decreased activity (25,28,35), whereas others indicated the opposite (16,40) or reported a modulation in its substrate specificity (24). Li et al (43) had identified Tyr-187 as a phosphorylation site in PKC␦ upon 12-O-tetradecanoylphorbol-13-acetate or platelet-derived growth factor stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that cross-talk among PTKs and Ser/Thr kinases occurs commonly in different cell types and serves as an important regulatory mechanism. In this regard, recent studies have shown that a novel PKC, PKC␦, can be phosphorylated on tyrosine residues upon activation (16). Because of the close structural relationship between PKC␦ and PKC (5) and the finding that PKC colocalizes to the activated TCR complex (which includes activated PTKs) in antigen-specific T cells (13), we have decided to examine whether PKC can become phosphorylated on tyrosine residues.…”
Section: Protein Kinase C (Pkc)mentioning
confidence: 99%
“…Much less is known about the regulation of the more recently discovered PKC 8, particularly at the mRNA level. PKC ~5 was shown to exert antiproliferative actions upon overexpression in CHO [7] or NIH 3T3 cells [8,9] and to cause differentiation in myeloid 32D cells [10]. PKC 8 is also a candidate for mediating the antiproliferative effects of phorbol esters observed in some pituitary and colon carcinoma cell lines [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…When overexpressed, it can slow the growth of fibroblasts (Mischak et al, 1993), and inhibit morphological transformation in a variety of systems (Li et al, 1996;Perletti et al, 1999). PKCd is phosphorylated on tyrosine residues in response to several different stimuli, usually as a result of SFK activity (Li et al, 1994;Denning et al, 1996;Blake et al, 1999;Kronfeld et al, 2000;Joseloff et al, 2002). SFKs processively phosphorylate several tyrosines on PKCd (with Tyr 311 being the first residue phosphorylated), and this causes the subsequent degradation of the protein.…”
Section: Other Sfk Mitogenic Targetsmentioning
confidence: 99%